2012
DOI: 10.3390/ijms131013414
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Breast Cancer Migration, Invasion and Metastasis

Abstract: MicroRNAs (miRNAs) are a major class of small, noncoding RNA molecules that regulate gene expression by targeting mRNAs to trigger either translational repression or mRNA degradation. They have recently been more widely investigated due to their potential role as targets for cancer therapy. Many miRNAs have been implicated in several human cancers, including breast cancer. miRNAs are known to regulate cell cycle and development, and thus may serve as useful targets for exploration in anticancer therapeutics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
132
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 125 publications
3
132
0
10
Order By: Relevance
“…Recently, the abnormal expression of miRNAs in several types of cancer has been confirmed, including colon cancer, hepatocellular carcinoma, lung cancer and breast cancer (5)(6)(7)(8). Emerging evidence has indicated that miRNAs function as oncogenes or tumor suppressor genes to control cell proliferation, invasion, migration, differentiation and apoptosis (9)(10)(11). For example, miR-638 has been shown to inhibit cell proliferation and invasion and to regulate the cell cycle by targeting tetraspanin 1 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the abnormal expression of miRNAs in several types of cancer has been confirmed, including colon cancer, hepatocellular carcinoma, lung cancer and breast cancer (5)(6)(7)(8). Emerging evidence has indicated that miRNAs function as oncogenes or tumor suppressor genes to control cell proliferation, invasion, migration, differentiation and apoptosis (9)(10)(11). For example, miR-638 has been shown to inhibit cell proliferation and invasion and to regulate the cell cycle by targeting tetraspanin 1 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenic miRNAs are often overexpressed in tumors and are termed "oncogenic" because they play similar roles as oncogenes during the process of cancer development. In addition, the expression of tumor suppressing miRNAs is often downregulated in tumors; these miRNAs are called tumor suppressor miRNAs because they function similarly to tumor suppressor genes (Tang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate signaling pathways at the post‐transcriptional level and are frequently deregulated in breast cancer. It has been shown that aberrantly expressed miRNAs promote cancer development, metastasis formation, and potently induce drug resistance in both tumor cells and cells of the tumor microenvironment (Bott et al ., 2017; Breunig et al ., 2017; Dvinge et al ., 2013; Tang et al ., 2012; Zhu et al ., 2011). In a previous study, we have identified a tumor‐suppressive function of the miR‐520/miR373 family by targeting TGFBR2 in breast cancer cells (Keklikoglou et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%